International Scientific and Practical Conference "AgroSMART - Smart Solutions for Agriculture" (AgroSMART 2018) 2018
DOI: 10.2991/agrosmart-18.2018.138
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Changes in Dogs and Cats With Ectoparasitosis in Northern Trans-Urals

Abstract: Skin is the most vulnerable and extensive body area in mammals. The clinical manifestation of dermatopathies may vary from minor irritation to extensive ulcers causing severe discomfort and disturbance of homeostasis. The aim of the research was to study the hematological status of dogs and cats with the most common ectoparasitosis of varying severity. The research was conducted in the period from 2015 to 2017 on the basis of the Department of Anatomy and Physiology of Northern Trans-Ural State Agricultural Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(5 reference statements)
1
2
0
2
Order By: Relevance
“…In the term of haematological examination (Table 1), results revealed significant (p≤0.001) reduction in HCT value, TEC and Hb level in affected cases compared with healthy dogs. These results were in agreement with (Tkacheva and Glazunova, 2018). Anemia was classified as macrocytic normochromic regenerative type with prominent anisocytosis.…”
Section: Ectoparasitic Infestation Related Anemiasupporting
confidence: 88%
“…In the term of haematological examination (Table 1), results revealed significant (p≤0.001) reduction in HCT value, TEC and Hb level in affected cases compared with healthy dogs. These results were in agreement with (Tkacheva and Glazunova, 2018). Anemia was classified as macrocytic normochromic regenerative type with prominent anisocytosis.…”
Section: Ectoparasitic Infestation Related Anemiasupporting
confidence: 88%
“…These findings are in agreement with findings of earlier researchers Saari et al (2009) [5] as they reported overall prevalence of demodicosis in cats 47.95%. Tkacheva and Glazunova (2018) [9] also reported overall prevalence of demodicosis in cats as 3.53 %.…”
Section: Overall Prevalencementioning
confidence: 92%
“…During feeding, Ticks secrete saliva in the dermis, which contains biologically active substances that cause an allergic reaction. When the tick punctures the skin of its host, it injects a substance that anesthetizes the attachment site and reduces the blood coagulability; However, most dogs and cats with ectoparasites have no clinical symptoms; thus, animal does not reflect any discomfort and does not feel the tick's presence (8,9,10). The Ixodes affect animal health entirely such as severe blood loss, serious hematological changes, decrease of some blood biochemical parameters, mineral levels and I Egyptian Journal of Veterinary Sciences https://ejvs.journals.ekb.eg/ trace elements [11].…”
Section: Introductionmentioning
confidence: 99%